Autopsy Discoveries in Severe Malaria - Mohammad Tegar Indrayana; Dedi Afandi; Ilhami Romus; Suri D. Lesmana (Faculty of Medicine Universitas Indonesia, 2023)
Severe malaria is a disease caused by Plasmodium falciparum as the main cause of death in malaria. As autopsy examinations on malaria are rare in Indonesia, we report a nineteen-year-old male from Dumai, Indonesia, who died of severe malaria on November 10th 2018, at Dumai Regional General Hospital of Riau Province. The diagnosis was concluded from autopsy, histopathology and toxicology. This case report aimed to explain autopsy findings in severe malaria. As the result of external examination, we found some bruises on the right earlobe, lip mucosa and lower leg; excoriations on the neck, both arms and right lower leg; excoriations on the right lower leg and blood infiltration in the connective tissue on the right intercostal space. The autopsy and histopathology examination showed signs of congestion and hemozoin pigment in the brain, small intestine, liver, lung, heart, kidney, stomach and spleen. On toxicology examination, there was no narcotic substance found. Based on autopsy findings, histopathology and toxicological findings, we conclude that the cause of death, in this case, was severe malaria. Blunt violence to the ears, lips, neck, arms, and legs did not significantly cause death.